ADVANTAGES OF USING INTEGRATIVE-COGNITIVE TASKS IN DEVELOPING PROFESSIONAL COMPETENCE IN FUTURE PRIMARY CLASS TEACHERS (Web of Teachers: Inderscience Research, 2024)
The high potential of the teaching staff directly serves as the basis for the perfect organization of the educational process. After all, the more competencies a teacher has developed, the better results he can achieve in his pedagogical activities. Among them, professional competence is the most necessary set of skills and qualifications for a teacher. This article presents several recommendations for the formation of such professional competences for future primary school teachers and, at the same time, to achieve their high level of improvement.